2018
DOI: 10.1097/j.pain.0000000000001429
|View full text |Cite|
|
Sign up to set email alerts
|

The association between multiple sclerosis and pain medications

Abstract: This study aimed to consider consequences of multiple sclerosis for patients in Sweden throughout various stages of the life course. The thesis was separated into four constituent papers, which dealt with different aspects of the disease, its symptoms, and implications at different life stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 145 publications
0
13
2
4
Order By: Relevance
“…At lik ta me ty ri me neu ro pa ti nis skaus mas pa si reið kë dau giau nei pu sei ti ria mø jø, daþ niau siai, kaip mi në ta, bu vo apa ti në se ga lû në se, daþ niau sias po bû dis -de gi nan tis. Lite ra tû ros duo me ni mis, neu ro pa ti nis skaus mas ran da mas dau giau nei pu sei ti ria mø jø ir yra daþ nes nis, ser gant progre suo jan èio mis li gos for mo mis, taip pat daþ nes nis jaunes niems þmo nëms [5,15,16]. Li te ra tû ro je nu ro do mas neu ro pa ti nio skaus mo po bû dis daþ niau siai yra elek tros sro vës pli ti mo, ant ro je vie to je -de gi nan tis [17].…”
Section: Rezultatø Aptarimasunclassified
See 3 more Smart Citations
“…At lik ta me ty ri me neu ro pa ti nis skaus mas pa si reið kë dau giau nei pu sei ti ria mø jø, daþ niau siai, kaip mi në ta, bu vo apa ti në se ga lû në se, daþ niau sias po bû dis -de gi nan tis. Lite ra tû ros duo me ni mis, neu ro pa ti nis skaus mas ran da mas dau giau nei pu sei ti ria mø jø ir yra daþ nes nis, ser gant progre suo jan èio mis li gos for mo mis, taip pat daþ nes nis jaunes niems þmo nëms [5,15,16]. Li te ra tû ro je nu ro do mas neu ro pa ti nio skaus mo po bû dis daþ niau siai yra elek tros sro vës pli ti mo, ant ro je vie to je -de gi nan tis [17].…”
Section: Rezultatø Aptarimasunclassified
“…Kuo di des nis skaus mas, tuo di des nis ir spastið ku mas. Tai pa ro do, kad neu ro pa ti nis skaus mas ir spastið ku mas yra glau dþiai su si jae: ga lû në je, ku rio je yra di desnis spas tið ku mas, pro gre suo ja ir neu ro pa ti nis skaus mas [16,17].…”
Section: Rezultatø Aptarimasunclassified
See 2 more Smart Citations
“…Individuals with MS experience a wide variety of symptoms, one of which is pain. Recently, we reported that MS patients are affected by pain, in particular neuropathic pain, to a greater extent than the general population through considering prescribed pain medications as a proxy for a pain diagnosis (1). The neuropathic pain in MS likely stems from the disease inherent lesions in the CNS (2).…”
Section: Introductionmentioning
confidence: 99%